Pension Age Which Would Guarantee Stabilization of the Old Age Dependency Ratio - Fiala, Tomáš; Langhamrová, Jitka (Wydawnictwo Uniwersytetu Ekonomicznego we Wrocławiu, 2017)
According to the current legislation the statutory retirement age in the Czech Republic should permanently increase with constant increment 2 months for each subsequent generation. This fact is very often criticized by both politicians and experts. A proposal of halting the rise in retirement age in 2030 at the threshold 65 years is discussed in the Parliament this year. The main reason for increasing the retirement age in the Czech Republic since 1995 was to eliminate the consequences of population ageing for increasing financial burden of the pension system. Because of this permanent increase the proportion of population size in retirement age and population size in productive age (old age dependency ratio) would be not so rapidly growing after 2040 when numerous generations born in the 70th will retire. The paper presents computations of the old-age dependency ratio in the Czech Republic for various variants of development of fertility, mortality, migration and retirement age in the case of the Czech Republic and for each variant also the retirement age threshold (changing in time) which would guarantee stabilization of the old-age dependency at its present time value
20-th AMSE. Applications of Mathematics and Statistics in Economics. International Scientific Conference: Szklarska Poręba, 30 August- 3 September 2017. Conference Proceedings Full Text Papers, s. 117-132
Keywords: old-age-dependency ratio; retirement age; population projection; the Czech Republic